2016
DOI: 10.4081/rt.2016.6124
|View full text |Cite
|
Sign up to set email alerts
|

Cancers in Young Patients in Uyo (Niger-delta Region of Nigeria): Magnitude of the Problem and Histopathological Prolife

Abstract: Cancers are thought to be rarer in younger population, but emerging data show an increasing incidence of these diseases. The aim of this study was to evaluate the clinicopathological characteristics of cancer among young patients (≥30 years) in Uyo, Nigeria. All specimens were collected and reviewed during the period January 2007-December 2012; complete clinicopathological data were also considered. A total of 108 cases of proven cancers were diagnosed (3.4%), accounting for 14.1% of all malignancies. A male:f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A survey of institutional registries cutting across 15 states in the 6 geopolitical zones of Nigeria, reported that in both sexes, breast cancer, cervical, liver prostate and colorectum in that order were the commonest among Nigerians [17].In males, prostate cancer, liver, Non-Hodgkin lymphoma colorectum and pancreas in that order, while in females, breast cancer, cervical, liver, colorectum and Non-Hodgkin lymphoma in that order were the commonest [17]. The pattern of childhood cancer in Nigeria is somewhat similar in most of the reported cases; Lymphomas (Hodgkin and Non-Hodgkin), are the commonest followed by Retinoblastomas and or Soft tissue tumours, or nephroblastoma [1,[18][19][20][21][22][23]. This study was aimed to get a trend analysis of cancer cases from the rest of Cross River State, not covered by the population-based Calabar cancer registry.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of institutional registries cutting across 15 states in the 6 geopolitical zones of Nigeria, reported that in both sexes, breast cancer, cervical, liver prostate and colorectum in that order were the commonest among Nigerians [17].In males, prostate cancer, liver, Non-Hodgkin lymphoma colorectum and pancreas in that order, while in females, breast cancer, cervical, liver, colorectum and Non-Hodgkin lymphoma in that order were the commonest [17]. The pattern of childhood cancer in Nigeria is somewhat similar in most of the reported cases; Lymphomas (Hodgkin and Non-Hodgkin), are the commonest followed by Retinoblastomas and or Soft tissue tumours, or nephroblastoma [1,[18][19][20][21][22][23]. This study was aimed to get a trend analysis of cancer cases from the rest of Cross River State, not covered by the population-based Calabar cancer registry.…”
Section: Introductionmentioning
confidence: 99%
“…Nigerian women aged 15 and above who are at risk of developing cervical cancer are 50.33 million, 14943 women are diagnosed and 10403 died yearly (Bruni, Albero, Serrano, Mena, G´omez, Mu˜noz, Bosch, de Sanjos´e, 2019). The worrisome rise in adolescent and young adult patients with malignant epithelial malignancies of the cervix is alarming among patients aged 0-30 years old, especially 21-30 years age group (Abudu & Akinbami, 2016).…”
Section: Introduction Cervical Cancer (Cc) Is Caused By a Sexually Ac...mentioning
confidence: 99%
“…There are 50.33 million Nigerian women aged 15 and older who are at risk of developing cervical cancer, 14,943 of whom are diagnosed, and 10,403 of whom die yearly [ 2 ]. The worrisome rise in adolescent and young adult patients with malignant epithelial malignancies of the cervix is alarming among patients aged 0–30 years, especially the 21–30 year age group [ 3 ].…”
Section: Introductionmentioning
confidence: 99%